Sentindo como brasileiro e maranhense: o SPILTN e a inserção do Maranhão na política indigenista nacional (1910) - AMORIM, Liana Rayssa Mota (2022)
This research aimed to discuss the process of implementation of the Serviço de Proteção ao Índio e Localização dos Trabalhadores Nacionais (SPILTN) in the state of Maranhão in 1910. From the understanding that the operation and execution of the plan of actions provided by the guidelines of the organ was directly influenced by the articulated relationship between national and local development demands. Therefore, with this research we sought to locate Maranhão geopolitically, through a setback in time, making it possible to verify which economic and social trends were debated by political representatives and how this reality imposed some important aspects for the composition of the scenario of application of the indigenist policy in the state. This scenario is relevant to the observation of the delineation that Indigenism took in lands of Maranhão, making possible the articulation of an auxiliary association of the Indigenist agency, the Gonçalves Dias Crusade, responsible for engaging various sectors of the Maranhão society, specifically individuals considered to be the main ones by professional and political occupations, around the noble task of protecting the Indians, showing how the zeal with the so-called brothers of the jungle was a republican and positivist society project that in its formulation little considered the native dynamics. Although fully visible and active, when observed the Northwest of Maranhão, the region of Turiaçu-Gurupi on the border between Maranhão and Pará, understood as problematic from the eighteenth to the twentieth century for having as quilombolas and indigenous population contingents, among the latter, highlighting the Ka'apor occupying a fundamental place in the narratives about the SPILTN in the state. This exercise was made possible by reading and analyzing the official documents of the organ, located in the collection available virtually from the National Museum of the Indian, with the sections dedicated to the indigenous question and others, such as labor and economy, in several editions of Maranhão's periodicals, accessed through the digital archive of the National Library. In order to understand how the economic, political, and social projects interfered with the installation of the Service in Maranhão, and to know how it was received by civil society and by the indigenous peoples, the targets of the activities.